Vaksin Covid-19 Sebagai Pemenuhan Hak Asasi Manusia - Aditya Candra Pratama Sutikno (Lex Renaissance, 2020)
The legal issue that lies in the outbreak of the Covid-19 pandemic is contained within the scope of medical law, which is a discussion on the quality of human life in the healthcare sector. In this case, the eradication of disease, cure of disease and recovery of disease, in order to realize the maximum degree of health in the community. Efforts are taken to overcome the current Covid-19 pandemic, one of which is done through vaccination. This study further examines from a legal perspective whether the Covid-19 vaccination program can be qualified as an effort to fulfill human rights. This is a normative legal research, with a conceptual approach and qualitative analysis. This research then concludes that vaccines are widely used to prevent various diseases and help fight certain diseases, by carrying out the Covid-19 vaccine as a form of recognizing and respecting the human rights of others, the right to a decent life, safety and the right to life, and the right to sustain life